Comparison of sexual function outcomes after vNOTES and laparoscopic tubal sterilization - Begum Ertan; Gokce Aykanat; Onur Yavuz; Ufuk Atlihan; Ferruh Acet (Frontiers in Medicine, 2026)
Objective To compare postoperative sexual function outcomes following vaginal natural orifice transluminal endoscopic surgery (vNOTES) and laparoscopic tubal sterilization (LTS). Material and Methods This retrospective comparative cohort analysis included 64 women with prospectively collected routine clinical data who underwent permanent surgical sterilization using vNOTES ( n = 31) or laparoscopy ( n = 33). Dyspareunia VAS, QSES, and FSFI scores were assessed preoperatively and at 6 months. Six-month outcomes were compared using ANCOVA adjusted for the corresponding baseline scores. Adjusted mean differences, 95% confidence intervals, and partial eta squared (partial η 2 ) were reported. Results After adjustment for baseline scores, the 6-month dyspareunia VAS score was significantly higher in the vNOTES group than in the LTS group (AMD, 0.44; 95% CI, 0.22 to 0.66; unadjusted p < 0.001; Holm-adjusted p < 0.002; partial η 2 = 0.210). No significant differences were observed in the primary outcome, total FSFI (AMD, -1.00; 95% CI, -2.70 to 0.70; p = 0.240), or in QSES (AMD, -0.40; 95% CI, -2.10 to 1.30; Holm-adjusted p = 0.640). Among the exploratory FSFI domains, only satisfaction remained significantly lower in the vNOTES group after Holm correction (AMD, -0.39; 95% CI, -0.61 to -0.17; Holm-adjusted p < 0.006). The unadjusted difference in lubrication did not remain significant after correction (Holm-adjusted p = 0.055). Conclusion vNOTES was associated with higher dyspareunia scores and lower satisfaction-domain scores at 6 months; however, no significant between-group differences were observed in total FSFI or QSES scores. These findings should be interpreted cautiously because of the retrospective, nonrandomized design and small sample size.